Developing a Process for Criteria-Led Discharge: Selection of Patients for Efficient and Effective Discharge (SPEED). Issue 2 (April 2020) - Lees-Deutsch, Liz; Jackson, Julia; Balaji, Ariyur; Topping, Annie
Abstract : Background: Criteria-led discharge (CLD) is an approach for maximizing bed capacity by expediting patient discharge. Problem: In acute medicine settings, patients commonly have multiple medical problems, which render single care pathway and clinical protocols of limited use. CLD offers potential, but little evidence exists about how to best implement it in these contexts. Approach: Retrospective case note analysis generated characteristics from patients' discharge plans to design a criterion-based framework to aid patient selection for CLD. These criteria were hypothetically tested on patient case notes (n = 50). Outcomes: CLD was identified as suitable (n = 27) and unsuitable (n = 23) from 50 case notes. Interrater agreement was 86% between 3 reviewers. Conclusions: This review has provided greater understanding of the complexity of discharge in acute medicine settings. Implementing CLD to optimize timeliness of patient discharge might offer a solution for selected patients. Abstract : Supplemental Digital Content is Available in the Text.